Recommendations for the use of antiretroviral therapy in adults living with human immunodeficiency virus in Singapore - Chiaw Yee Choy; Chen Seong Wong; P Arun Kumar; Dariusz Piotr Olszyna; Yii Ean Teh; Mei Fong Jaime Chien; Asok Kurup; Yin Ling Koh; Lai Peng Ho; Hwa Lin Law; Nathalie Grace Sy Chua; Hui Yan Joy Yong; et al. (Singapore Medical Journal)
Since the advent of combination antiretroviral therapy (ART), the mortality attributable to human immunodeficiency virus (HIV) infection has decreased by 80%. Newer antiretroviral agents are highly efficacious, have minimal side effects as compared to older drugs, and can be formulated as combination tablets to reduce patients’ pill burden. Despite these advances, 680,000 people worldwide died of acquired immunodeficiency syndrome-related illnesses in 2020. The National ART and Monitoring Recommendations by the National HIV Programme have been created to guide physicians on the prescribing of ART based on the patients’ needs. These recommendations are based on international guidelines and tailored to the local context and unique domestic considerations. We hoped that with the publication of these recommendations, the care of people living with HIV can be enhanced, bringing us closer to ending HIV in our lifetime.